Development of Interactive Ebooks as Independent Learning in Micro Teaching Courses at Mahasaraswati University Denpasar - Ni Wayan Eminda Sari; IGAP Tuti Indrawati; AA Rai Laksmi; Ni Putu Saptari Maryani; Maria Sri Rosari (Lembaga Bale Literasi, 2026)
This research aims to develop and validate interactive ebooks as an independent learning medium in Micro Teaching courses at Mahasaraswati University Denpasar. The background is based on findings that Micro Teaching lectures are still carried out conventionally and have not optimized students’ independent learning, even though this course plays a strategic role in shaping prospective teachers’ basic teaching skills before the School Field Program (PLP). This research uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The analysis stage involved observation and interviews to identify student needs, followed by the design and development of products referring to the course RPS. The resulting product is an interactive ebook containing materials on basic teaching skills, exercises, summaries, and formative tests. Validation was conducted by material experts, media experts, and learning design experts using questionnaire instruments, with quantitative and qualitative descriptive data analysis. The validation results showed that the interactive ebook achieved a validity score of 92% from material experts, 88% from media experts, and 90% from learning design experts (all in the “valid” category, 80.01–99.99%). The practicality test by students obtained a score of 85% (practical category). Thus, the interactive ebook developed is empirically valid and practical, making it suitable for use as an alternative independent learning medium in Micro Teaching courses.